2011
DOI: 10.1016/j.bcp.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Stable formyl peptide receptor agonists that activate the neutrophil NADPH-oxidase identified through screening of a compound library

Abstract: The neutrophil formyl peptide receptors (FPR1 and FPR2) are G-protein coupled receptors that can induce pro-inflammatory as well as anti-inflammatory activities when activated. Accordingly, these receptors may become therapeutic targets for the development of novel drugs to be used for reducing the inflammation induced injuries in asthma, rheumatoid arthritis, Alzheimer's disease, cardiovascular diseases and traumatic shock. We screened a library of more then 50 K small compounds for an ability of the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…The surface consists of three regions (H 1 , H 2 , and H 3 ), which correlate with subpockets I, II, and III in the FPR2 binding site, respectively ([12] and Figure 5) . Enantiomeric FPR2 agonists and their active/inactive counterparts reported here and published previously [9;13;15] were then compared to the pharmacophore model. All molecules were overlaid in the three-subpocket model, and the highest-score superimpositions together with values of calculated similarity are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The surface consists of three regions (H 1 , H 2 , and H 3 ), which correlate with subpockets I, II, and III in the FPR2 binding site, respectively ([12] and Figure 5) . Enantiomeric FPR2 agonists and their active/inactive counterparts reported here and published previously [9;13;15] were then compared to the pharmacophore model. All molecules were overlaid in the three-subpocket model, and the highest-score superimpositions together with values of calculated similarity are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…166 All 90 compounds with a given EC 50 were aniline derivatives covered by formula II and, according to the chemistry, were either cis-endo or cis-exo. 144 and 15, a FPR2 agonist discovered earlier 165 and used as comparator. In further studies, 11, 13, and Amgen compound 6 were shown to activate neutrophils preferentially through FPR1.…”
Section: Fpr2/alxr As a Target For The Roimentioning
confidence: 99%
“…This means that SDS might provide useful information about ligand-binding sites for particular protein targets. For example, SDS modulates the activity of the neutrophil formyl-peptide receptor (Thoré n et al, 2010); this G-protein-coupled receptor is an important therapeutic target for anti-inflammatory agents and selective antagonists have potential utility in the treatment of many pathological processes, including rheumatoid arthritis, sepsis, septic shock, asthma and Alzheimer's disease (Forsman et al, 2011). SDS might provide a useful new lead compound in the effort to develop such agents.…”
Section: Figurementioning
confidence: 99%